2007
DOI: 10.3733/ucanr.7249
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fertility Management for Organic Crops

Abstract: The University of California prohibits discrimination or harassment of any person on the basis of race, color, national origin, religion, sex, gender identity, pregnancy (including childbirth, and medical conditions related to pregnancy or childbirth), physical or mental disability, medical condition (cancer-related or genetic characteristics), ancestry, marital status, age, sexual orientation, citizenship, or status as a covered veteran (covered veterans are special disabled veterans, recently separated veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…These values are higher than those obtained by Schmitt and Rehm [22]. Gaskell et al found 2-3% of N, but only 1.5% of phosphorous and potassium in chicken manure [23]. Because poultry manure is usually stored for varying lengths of time and is mixed with litter material when it is obtained from floor pens, it will vary in composition.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These values are higher than those obtained by Schmitt and Rehm [22]. Gaskell et al found 2-3% of N, but only 1.5% of phosphorous and potassium in chicken manure [23]. Because poultry manure is usually stored for varying lengths of time and is mixed with litter material when it is obtained from floor pens, it will vary in composition.…”
Section: Discussionmentioning
confidence: 78%
“…It allows keeping soil fertility, while improving soil structure and availability of mineral elements. In fact, the increase in soil organic matter to optimum levels is a key aspect of any organic production system [23]. The locally produced poultry manure is available in good quantity and for all social groups and it seems to be economically more profitable than more expensive mineral manure.…”
Section: Discussionmentioning
confidence: 99%
“…Growing legume cover crops is generally the most economical way to provide plant-available N in organic systems (Gaskell et al 2000b). However, organic growers often use other methods to augment soil nitrogen supply (Hartz and Johnstone 2006).…”
Section: Nutrientsmentioning
confidence: 99%
“…applied to them. The bioassays are performed to check the components present in the plants and the growth of the plants were checked, followed by total carbohydrates [7] , total protein [8] , total lipid [9] , total phenol [10] , total chlorophyll and total carotenoids [11] were also estimated.…”
Section: Application Of Fertilizer Samples To the Crop Grownmentioning
confidence: 99%